The pathogenetic basis for a disease continuum in early- and late-onset ataxia-dystonia supports a unified genetic diagnostic approach. (March 2023) - Garofalo, M.; Vansenne, F.; Verbeek, D.S.; Sival, D.A.
Abstract: Introduction: Genetically inherited ataxic disorders are classified by their age of disease presentation into early- and late-onset ataxia (EOA and LOA, presenting before or after the 25th year-of-life). In both disease groups, comorbid dystonia co-occurs frequently. Despite overlapping genes and pathogenetic features, EOA, LOA and dystonia are considered as different genetic entities with a separate diagnostic approach. This often leads to diagnostic delay. So far, the possibility of a disease continuum between EOA, LOA and mixed ataxia-dystonia has not been explored in silico. In the present study, we analyzed the pathogenetic mechanisms underlying EOA, LOA and mixed ataxia-dystonia. Methods: We analyzed the association of 267 ataxia genes with comorbid dystonia and anatomical MRI lesions in literature. We compared anatomical damage, biological pathways, and temporal cerebellar gene expression between EOA, LOA and mixed ataxia-dystonia. Results: The majority (≈65%) of ataxia genes were associated with comorbid dystonia in literature. Both EOA and LOA gene groups with comorbid dystonia were significantly associated with lesions in the cortico-basal-ganglia-pontocerebellar network. EOA, LOA and mixed ataxia-dystonia gene groups were enriched for biological pathways related to nervous system development, neural signaling and cellular processes. All genes revealed similar cerebellar gene expression levels before and after 25 years of age and during cerebellar development. Conclusion: In EOA, LOA and mixed ataxia-dystonia gene groups, our findings show similar anatomical damage, underlying biological pathways and temporal cerebellar gene expression patterns. These findings may suggest the existence of a disease continuum, supporting the diagnostic use of a unified genetic approach. Highlights: Anatomical damage to the cortico-basal-ganglia-pontocerebellar network is associated with comorbid dystonia in both EOA and LOA gene groups. EOA, LOA and mixed ataxia-dystonia gene groups share biological pathways of brain development, neural signaling, and cellular processes. The clinical classification into EOA and LOA is not reflected by different gene expression patterns before or after 25 years of age. Our findings in EOA, LOA and mixed ataxia-dystonia point to a shared disease continuum. Our findings question the clinical relevance of classifying and diagnosing ataxia as separate EOA, LOA and/or comorbid dystonia disease groups.